The relationship between economic growth, foreign direct investment and unemployment in Central Asia: A vector autoregressive model approach - Anh Tru Nguyen (Journal of Contemporary Economic and Business Issues, 2019)
The article investigates the relationship between economic growth, foreign direct investment and unemployment in five Central Asian countries between 1997 and 2016. We found that GDP has a positive relationship with FDI and this implies that the growth of GDP in Central Asian countries has attracted more FDI inflows. However, GDP negatively affects FDI in lag 4 and this reflects the fact that the growth of GDP in this region depends on other variables rather than FDI. Moreover, this result also suggests that the use of FDI to boost economic growth of Central Asian countries is ineffective. Results also indicate that FDI has a negative influence on unemployment and this implies that an increase of FDI can contribute to reducing the unemployment rate in Central Asia. We also found that GDP and unemployment do not cause other variables, while FDI causes other variables. Lastly, results indicate that there is a co-integration among variables.
Keywords: E22; E24; F43; 330; Economic Growth; Foreign Direct Investment; Unemployment; Central Asia